Evaluation of the effect of cattle slurry on the production of Taiwan grass (Pennisetum purpureum) in an Andisol soil - Rojas-Molina, Lourdes (2020)
Chemical fertilization has intensified in recent years and one of the biggest concerns is the poor efficiency of the use of nitrogen fertilizers and the environmental costs due to the losses of this element, which has motivated the implementation of low-input systems such as the practice of applying slurry, which can include manure, cleaning waters, rainwater, concentrate residues and litter waste, in order to provide nutrients to the forages that are produced for feeding animals. The objective of this study was to evaluate the quality of the slurry generated at the Alfredo Volio Mata Experiment Station and to determine the effect of its application on the soil and on the productive performance of Taiwan grass (Pennisetum purpureum cv. Taiwan). For the experiment, an area of 225 m2 planted with Taiwan grass was used which was divided into three large blocks and each block was subdivided into three plots that corresponded to the different nitrogen fertilization treatments at an equivalent dose of 300 kg/ha/year distributed in three applications. Each plot was 25 m2 (5 x 5 m). The treatments used were: 1) the control (0 kg of nitrogen), 2) slurry and 3) urea (46% of N). Soil samples were taken to perform an analysis at the beginning and at the end of the experiment, which included chemical-physical and microbiological characterization. The chemical analysis carried out on the slurry reports relatively low values of N, P and K (0.04, 0.01 and 0.04%, respectively). No significant changes were observed in terms of the chemical properties of the soil when comparing the analyzes carried out before and after the application of the different treatments. Regarding yield and nutritional quality of the forage, only statistically significant differences (P<0.05) were found for the percentage of CP where the treatments with urea and slurry presented the highest concentration of CP in the whole plant.